Civil Service Reform in the States - J. Edward Kellough , Lloyd G. Nigro (State University of New York Press, 2006)
Government jurisdictions in the United States have frequently reformed their administrative systems as they have struggled with changing political and economic circumstances. These administra- tive reforms are typically designed to reflect popular new models or emerging paradigms for public management. They are driven by complex and not necessarily congruent combinations of values and purposes ranging from the purely partisan to the largely technical. During the twentieth century, for example, there were at least twelve highly visible efforts to reform federal administrative arrange- ments—about one every eight years.1 There were also innumerable similar reforms enacted by state and local governments. With each reform, changes, both large and small, in the administrative machin- ery of government are implemented, and the effects of those changes often last long after the reform itself has become a distant memory. It is interesting to observe that, more often than not, public person- nel or civil service systems are at the top of the reform agenda.